Chromium (VI) removal from water using starch coated nanoscale zerovalent iron particles supported on activated carbon. Issue 6 (3rd June 2019) - Ji, Bin; Shu, Yaorong; Li, Yuexin; Wang, Jiale; Shi, Yuting; Chen, Wei
Abstract: Starch coated nanoscale zerovalent iron (S-nZVI) was immobilized in activated carbon (AC) and its Cr (VI) removal characteristics were studied. Macroscopic evidence and mechanism analysis proved that S-nZVI and AC were closely linked and mutual complementary. Different factors including pH of the original solution, reaction time, and mass ratio (S-nZVI@AC/Cr =10:1, 20:1, 30:1, 50:1, 60:1, 70:1) were studied to analyze the removal rate. Results showed that the removal rate of Cr (Ⅵ) could reach 99.96% under the condition of pH of 5, and temperature =25 °C, when the mass ratio of S-nZVI@AC/Cr was 60:1. The removal of Cr(Ⅵ) by S-nZVI@AC followed pseudo-second-order kinetics. X-ray diffraction (XRD) resulted demonstrate that S-nZVI@AC existed in a Fe3 C state before reaction and in a Fe(III) state after reaction. XPS (X-ray photoelectrons spectroscopy) analysis suggested that the mechanism of Cr (VI) removal by S-nZVI@AC is adsorption and reduction. S-nZVI@AC might be a potential composite material for the purification and detoxification of Cr (VI) in water because of its efficiency and stability.